Use of kombucha culture in the production of fermented dairy beverages. (February 2021) - Sarkaya, Pınar; Akan, Ecem; Kinik, Ozer
Abstract: Kombucha is a beverage obtained by fermenting tea containing sugar as a result of the symbiotic relationship between yeast and acetic acid bacteria. In this study, milk and various herbal teas (sage, blackberry, and green tea) were mixed in the ratio of 60:40 (v/v) and fermented with kombucha culture. 2.2-Diphenyl-1-picrilhydrazyl (DPPH) radical scavenging activity, total phenolic content, total reducing sugar content, and the microbiological and sensory properties of the fermented dairy beverage were examined. The highest DPPH radical scavenging activity was observed on the 1st day of storage of the blackberry tea-blended fermented beverage (98.48%), and the highest total phenolic content was observed on the 30th day of the green tea-blended fermented beverage (81.51 mg/mL). The maximum amount of glucuronic acid (0.42 g/100 mL) was observed on the 20th day of storage in the sage-blended fermented dairy beverage. The most favorite product was the blackberry blend, whereas the least favorite was the dairy beverage (control sample) fermented with kombucha based on sensory scores. This study demonstrates that milk and herbal teas could be successfully fermented with kombucha culture, thereby improving its functional properties. Highlights: Milk and herbal teas were successfully fermented with kombucha culture. The maximum glucuronic acid was detected in sage-blended fermented dairy beverage. The sucrose and lactose content of all samples were higher than d -glucose content. The most favored beverage was blackberry-milk blended product.